Effect of Different Vitamin D Levels on Cognitive Function in Aged Mice After Sevoflurane Anesthesia - Zhang, Jialei; Zhang, Xiaoling; Yang, Yongyan; Zhao, Jun; Hu, Wenqing; Yu, Yonghao (Frontiers in Aging Neuroscience, 2022)
Although the biological relationship between vitamin D (VD) deficiency and cognitive function has been recognized by many scholars, the theoretical mechanisms involved are still not well-understood. In this study, we demonstrated the role of VD in alleviating the cognitive dysfunction in aged mice caused by sevoflurane anesthesia. Forty female C57BL/6 mice aged 12 months were selected for the experiment. VD (-) and VD (+) mouse models and sevoflurane anesthesia models were established. Mice were randomly divided into normal elderly group (NC group), normal aged mice + sevoflurane anesthesia treatment group (NS group), aged VD (-) mice + sevoflurane anesthesia treatment group [VD (-) group], and aged VD (+) + sevoflurane anesthesia treatment group [VD (+) group]. To compare the emergence time after sevoflurane anesthesia in aged mice with different levels of VD and to test the cognitive function of four groups through the water maze. Inflammatory factor expression and cholinergic activity in hippocampus tissue of all mice were measured at the end of behavioral tests. These data show that, low levels of VD aggravated the delayed emergence and cognitive dysfunction in aged mice caused by sevoflurane anesthesia, while higher levels of VD mitigated this impairment by enhancing cholinergic activity and reducing inflammatory factor expression in the hippocampus.